DESAIN EVALUASI PROGRAM TRANSFORMASI DIGITAL SEKOLAH DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DAN MUTU LULUSAN - Muhammad Zulfahmiansyah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Digital transformation in schools has emerged as a strategic effort to improve learning effectiveness, educational management efficiency, and graduate quality. However, the implementation of educational technologies such as Learning Management Systems (LMS), artificial intelligence, and school information systems is often not accompanied by a comprehensive evaluation framework, making it difficult to objectively measure their impact on learning outcomes and graduate competencies. The limited availability of studies specifically addressing evaluation design for school digital transformation highlights the need for a systematic framework to support decision-making and continuous program improvement. This study aims to formulate a comprehensive evaluation design for school digital transformation programs to assess implementation effectiveness and their contribution to enhancing learning quality and graduate outcomes. This research employed a library research approach by reviewing books, policy documents, and scientific articles related to program evaluation, digital transformation, digital literacy, and educational quality assurance. Data were analyzed using content analysis techniques involving data reduction, categorization, interpretation, and theoretical synthesis. The findings indicate that an effective evaluation design should integrate the CIPP and Countenance Stake models to assess infrastructure readiness, teachers’ Technological Pedagogical Content Knowledge (TPACK), digital learning processes, students’ digital literacy, and program impacts on learning achievement and graduate quality. In conclusion, an integrated evaluation design can serve as an accountable and sustainable framework for optimizing school digital transformation and improving educational quality in the digital era. ABSTRAK Transformasi digital di sekolah berkembang sebagai strategi untuk meningkatkan efektivitas pembelajaran, efisiensi tata kelola pendidikan, dan mutu lulusan. Namun, implementasi teknologi pendidikan seperti Learning Management System (LMS), kecerdasan buatan, dan sistem informasi sekolah sering kali belum disertai desain evaluasi yang komprehensif, sehingga dampak program terhadap kualitas pembelajaran dan lulusan sulit diukur secara objektif. Keterbatasan kajian yang secara khusus merumuskan desain evaluasi transformasi digital sekolah menunjukkan pentingnya pengembangan kerangka evaluasi yang sistematis sebagai dasar pengambilan keputusan dan perbaikan program. Penelitian ini bertujuan merumuskan desain evaluasi program transformasi digital sekolah yang mampu mengukur efektivitas pelaksanaan program serta kontribusinya terhadap peningkatan mutu pembelajaran dan kualitas lulusan. Penelitian menggunakan pendekatan studi kepustakaan (library research) dengan menelaah buku, dokumen kebijakan, dan artikel ilmiah terkait evaluasi program, transformasi digital, literasi digital, dan penjaminan mutu pendidikan. Data dianalisis menggunakan teknik analisis isi melalui proses reduksi, kategorisasi, interpretasi, dan sintesis teoritis. Hasil kajian menunjukkan bahwa desain evaluasi yang efektif perlu mengintegrasikan model CIPP dan Countenance Stake untuk menilai kesiapan infrastruktur, kompetensi TPACK guru, proses pembelajaran digital, literasi digital siswa, serta dampaknya terhadap hasil belajar dan mutu lulusan. Kesimpulannya, desain evaluasi yang terintegrasi dapat menjadi dasar yang akuntabel dan berkelanjutan dalam mengoptimalkan transformasi digital sekolah guna meningkatkan kualitas pembelajaran dan mutu lulusan di era digital.